Synthesis, Spectral and Antibacterial Studies on Rare-Earth Metal Complexes with 1-Hydroxy-1-phenyl-3-benzoyl-2-thiourea - Swami, V.K.; Mathur, S.P. (Asian Journal of Chemistry, 2010)
1-Hydroxy-1-phenyl-3-benzoyl-2-thiourea (HPBT) and its complexes with Y(III), Sm(III) and Gd(III) were synthesised and screened for their antibacterial activity against some gram positive as well as gram negative bacteria. All the metal complexes possessed good antibacterial activity against E. coli, staphylococci and streptococci species. The newly synthesised complexes have been characterised by elemental analysis and spectral studies.